Bioaccumulation of copper and lead in Asian clam tissues from Bung Boraphet Reservoir, Thailand - Tinnapan Netpae (2018)
Bung Boraphet is the largest fresh water reservoir in Thailand. The accumulations of copper (Cu) and lead (Pb) in water, sediment and tissues of Asian clam (Corbicula sp.) with in Bung Boraphet were carried out to indicate possible polluting effect of soil erosion and the dissolution of water soluble salts from Nan river. Samples were collected from 12 study sites with in Bung Boraphet between February to December 2008. Cu and Pb in water were found at low levels but the heavy metals were detected at high levels in the sediment and tissues of Corbicula sp. Accumulation rate of Cu and Pb in tissues Corbicula fluminea was to determine under laboratory condition. Pb was accumulated in tissue more than Cu. The maximum 168 h Pb accumulation in tissues was found as 129.5 μg g-1 dry weight, whereas the Cu accumulation was maximum at 120 h as 26.83 μg g-1 dry wt.